Adolescent Perceptions of Conflict in Interdependent and Disengaged Friendships - Shulman, Shmuel (2002)
Interdependent and disengaged friendships in a middle-class sample of suburban Israeli adolescents were examined for differences in reports of conflict behavior. A total of 194 (100 females, and 94 males) close, reciprocal friends participated in a joint problem-solving task used to categorize friendships. Interdependent friends balanced closeness and individuality by cooperating on the task, whereas disengaged friends emphasized individuality by working independently on the task. In separate interviews, these friends recounted their most important conflict from the previous week. Older adolescents (M = 17.4 years) reported more conflicts over private disrespect than did younger adolescents (M = 12.7 years), whereas younger adolescents reported more conflicts over public disrespect and undependability than did older adolescents. Differences between friendship types in conflict initiation, negative affect, and relationship impact were found among older adolescents but not younger adolescents; differences in conflict resolutions were found in both age groups. In contrast to disengaged friends, interdependent friends were better able to manage conflicts in a manner that emphasized relationship harmony over individual gain.